(3GdeaGNQI Hf GdoMQI hGdCeIs - (3TYHGf Hf Sdje Hf YKeGf GdQhej GdUfYGfj,J (B1149 (3g` s
(3ChdgG (B:s
(3ef HYO MeO Gddg hGdUdGI Ydi GdfHj GdeNJGQ Pj GdUdGI eMeO eY Bdg GdcQGe eG ZQOJ hQbG Ydi HTGe s
(3BNQgG (B:s
(3hCdg eG SLY GdgRGQ heGJhG Edi Gddjd hGdfgGQ GfJgJ GdeaGNQI Hjf GdoMQI hGdCeI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH GdKGfjs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGfj YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B3 - (3U (B164 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B4 - (3U (B300 ; (3gOjI GdYGQajf ddHZOGOi(B: (3L (B1 - (3U (B417s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B71 s
Keywords: (3GdCOHs